Results of an alcohol breath tests campaign in a sample of construction site workers in Umbria region - Miscetti, Giorgio; Abbritti, Emilio Paolo; Bodo, Patrizia; Lumare, Alessandro; Romano Gargarella, Lea (La Medicina del Lavoro, 2015)
Objective: The purpose of the research was to evaluate the respect of the regulation on the prohibition of alcohol consumption in the building sector through an alcohol breath test campaign, and to acquire information on the alcohol consumption by the contractors. Methods: In the course of the investigation which covered the period 2011-2013, in a sample of construction, it was decided to access with verification of the presence of alcoholic beverages, administration workers to an anonymous questionnaire on alcohol consumption, execution of alcohol breath test. Results: The reached population consisted in 1635 subjects, 1040 of which Italians and 595 foreigners; the consumers of at least 0,5 AU/die resulted being 354 among Italians and 250 among foreigners (p0,05) between foreigners and Italians. Notwithstanding, among the negative subjects, 9% declared having consumed alcoholics during the meal immediately preceding the work shift; all this underlining a sound dangerous behaviour. A behaviour which may easily escape to an alcohol metric test, considering the relationship between the timing of the last alcohol consumption, the quantity assumed, the test timing and its result. Conclusions: The authors conclude pointing out how, in the studied sector, there certainly is a great tendency to respect the regulation on the prohibition of alcohol consumption, and how there is a reliable modification with regards to alcohol among the behavioural models traditionally allocated to building contractors, with a strong reduction of consumption as in working as in non-working hours. Notwithstanding, the authors may want to underline the persistency of dangerous behaviours worthy promotion, information and education actions. Besides, they advise and wish for additional interventions by the legislator, directed to better define the boundaries of the prohibition and impose in such boundaries an alcohol test level equal to 0 during the working hours.